SCIENTIFIC APPROACH TO STUDY OF AL-QURAN MATHEMATICS - Kefi Miftachul Ulum Kefi (Universitas Islam Indonesia, 2023)
The purpose of humans' creation in the world is none other than to worship Allah SWT and become caliphs on earth, which is explicitly stated in the Qur'an. Implicitly, there are two aspects of the purpose of human creation, namely the aspect of spirituality as a form of human servitude as a servant to their God and the aspect of intellect as a form of differentiating humans from other living things and as a leader on earth. Formation of spiritual aspects based on religious dogmas as doctrines, as well as intellectual aspects based on religious dogmas using rationality and empiricism approaches.The intellectual aspect is formed with an emphasis on science, one of which is mathematics, particularly sub-logic, reasoning, and more as the initial foundation for leadership on a micro- to macroscales.